76‐5: Invited Paper: Sensor Integration into a Multifunctional µLED Display ‐ New Paradigms - Minixhofer, Rainer; Drolet, Jean-Jacques (SID International Symposium Digest of technical papers, 2024)
With the advent of µLED displays, multiple paradigm shifts in the overall system architecture will offer new opportunities and dramatically change the requirements of display management and general sensing. This work focuses on the required system architecture of a microLED display with embedded sensing functionality.